EFIKASI DIRI AKADEMIK, DUKUNGAN SOSIAL ORANGTUA DAN PENYESUAIAN DIRI MAHASISWA DALAM PERKULIAHAN - Prastihastari Wijaya, Intan (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. The main purpose of this research is to know whether there is connection between self efficacy academic and social support parents with self adaptation of University Students. The research subject was 100 University Nusantara PGRI Kediri students consisting of 42 boys and 58 girls which was taken random and having caractesistis of the first grade of the University students and staying together with their own parents. The data of the self adaptation of the University students was obtained from the scale of self actualization. The data of the scale self efficiacy academic was also obtained from the scale of self efficacy academic. The data of social support parents was received from the scale of social support parents. The resulf of this analysis of multiple regression are from maximum R = 0,684; F = 42,717; p = 0,000 (p < 0,01). The resulf of this data analysis showing that the self efficacy academic and social support are integrated to self adaptation of the University students. The result of the analysis academic self efficacy correlation with self actualization of the University students was obtained r partial = 0,632; t = 8, 039 with p = 0,000 (p < 0,01). This data shows that there is positive correlation between academic self efficacy and self actualization. The hypothesis of the research classifying that there is correlation between them and it is acceptable. The out come of the analysis social support parents correlation with self adaption of the University students was attained r partial = 0,159; t = 1,582 with p = 0,117 (p > 0,05). This data indicates that the variable of the social support is isolated and it is not related to the self adaptation. The hypothesis of the research indicates that there is positive connection between social support and self actualization and there fore it is unacceptable or avoided. This is because of another factor that influences self adaptation of the University students a part from social support of the parents.Â Key word: Self adaptation, Self efficacy academic, Sosial support parents.Â